2001
DOI: 10.1080/02656730150201606
|View full text |Cite
|
Sign up to set email alerts
|

RF hyperthermia array modelling; validation by means of measured EM-field distributions

Abstract: The accuracy of a hyperthermia treatment simulation determines its role in prospective treatment planning and dosimetry for the individual patient. Of importance are (1) the accuracy of the numerical simulation method, and (2) the numerical description of the hyperthermia treatment system. The accuracy of the numerical method is generally determined by analysis of a problem that is analytically solvable. The validity of the description of the hyperthermia system is to be investigated by comparison of the simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Two outstanding challenges in EM phased-array hyperthermia are (1) to selectively elevate the temperature in the cancerous tissue without excessively elevating the temperature of the surrounding healthy tissues in the presence of electrical and thermodynamic inhomogeneities, and (2) to react to unexpected changes in the patient positioning and physiology (e.g., sudden change in blood flow in the tumor) that can significantly impact the quality of the delivered treatment. 192,193 Significant research progress has been obtained recently in heating devices appropriate for deep hyperthermia including ultrasonic arrays, [194][195][196][197][198][199][200][201][202][203][204][205][206][207][208] RF arrays, 105,[209][210][211][212][213][214][215][216] and microwave arrays. 39,137,191,192,193, Petrovich et al 240 have reported the results of a 14-institution trial conducted in the United States that employed the annular phased array system for regional hyperthermia production in 353 patients with advanced, recurrent, or persistent deep-seated tumors.…”
Section: Multielement Array Applicatorsmentioning
confidence: 99%
“…Two outstanding challenges in EM phased-array hyperthermia are (1) to selectively elevate the temperature in the cancerous tissue without excessively elevating the temperature of the surrounding healthy tissues in the presence of electrical and thermodynamic inhomogeneities, and (2) to react to unexpected changes in the patient positioning and physiology (e.g., sudden change in blood flow in the tumor) that can significantly impact the quality of the delivered treatment. 192,193 Significant research progress has been obtained recently in heating devices appropriate for deep hyperthermia including ultrasonic arrays, [194][195][196][197][198][199][200][201][202][203][204][205][206][207][208] RF arrays, 105,[209][210][211][212][213][214][215][216] and microwave arrays. 39,137,191,192,193, Petrovich et al 240 have reported the results of a 14-institution trial conducted in the United States that employed the annular phased array system for regional hyperthermia production in 353 patients with advanced, recurrent, or persistent deep-seated tumors.…”
Section: Multielement Array Applicatorsmentioning
confidence: 99%
“…The EM-field in the patient generated by the four (N Âź 4) individual applicators of the hyperthermia treatment apparatus at our institute is calculated by the CGFFT method [10]. This method has been described elsewhere [11,12].…”
Section: Delineating the Potential Hot Spotsmentioning
confidence: 99%
“…Some waveguides used as hyperthermia applicators are the ridged waveguides, [6] the AMC-4 array [7] and the two tilted waveguide [8]; however, all of them are fed by monopole antennas [1,[6][7][8]. There are performance studies of monopoles proposed for ISM-band applications, which have been used in the design of feeders for microwave antennas [9,10].…”
Section: Introductionmentioning
confidence: 99%